La disolución familiar afecta el rendimiento académico de los estudiantes de la escuela general básica nivel superior cyber school de la ciudad de Guayaquil - Guerrero Saldaña, Vanessa Ivonne (2013)
The family dissolution corresponds to the breakdown of the family unit, where the children are often the most vulnerable. Children who have recently experienced dissolution of the family can see affected the academic and social expectations in school. However, there is much variability in the children's adaptation to their parents' divorce, under some circumstances, children of divorced parents show only small negative effects that are limited in time, while in other cases the children are to adapt to the effects of parental divorce. Despite this resistance, many children who come from broken families demonstrate long-term effects, which have an impact on their performance at school, this in turn severely damaged its ability to develop and maintain a social relationship and lasting mutual…….